PENGARUH METODE LATIHAN FLOATING SERVICE TERHADAP KETEPATAN SERVIS ATAS PEMAIN BOLA VOLI PUTRI SMP - Ikhsan Maulana Putra; Refril Dani; Imam Suhatman (LP3M Universitas Muhammadiyah Muara Bungo, 2022)
This research is motivated by the lack of accuracy between the ball and the hand, the lack of variations in the form of training, the lack of training methods and the lack of knowledge of the correct service. The purpose of this study was to determine the effect of the floating service training method on service accuracy for female volleyball players at SMP Negeri 5 Rantau Pandan. The method used in this study is the experimental population method in this study 64 students, the sample amounted to a sample of 12 students. The design used in this is One Group Pretest and Posttest. The data analysis technique in this study used a hypothesis test (t-test) with a significance level of 0.05%. The results obtained in the initial test an average of 15.8 points and the final test 22.8 points. While th (7.45) and tt (1.796). Based on the results of the research that has been done, it can be concluded that the floating service training method on service accuracy for female volleyball players at SMP Negeri 5 Rantau Pandan there is a significant increase.